Green technology for livestock production: stepping into global climate change - Alimon, Abdul Razak (Malaysian Society of Animal Production, 2015)
Livestock production as an industry is facing great challenges not only in terms of increased demand of livestock products, disease control, animal welfare, feed availability but also global climate change. The IPCC is fully convinced that globally there has been an increase in world temperature that leads to climate change. In fact, the last decade has shown enormous fluctuation in animal and feed production due to floods, lengthy droughts and extreme weather conditions. This phenomenon has been associated with increase in global temperature, and possible melting of the ice-caps. Some scientists have indicated that methane production by ruminants contribute substantially to greenhouse gases. To mitigate emission of green house gases that cause global warming, several steps have been taken by many countries especially reducing carbon footprint, reduction of using fossil fuels, and developing green technology. This paper describes some of the thoughts on how green technology is important for the sustainability of livestock production. The practice of precision farming will be more enhanced with the use of green technology. With the development of new techniques in harnessing the sun’s energy, the use of fossil fuels can be greatly reduced. Adaptation to the climate change require substantial amount of energy, and green technology with adapted farming system may be the answer to sustain animal products as a part of human diet in future.